Evaluation and Mapping of the Impact of Factory Development on Road Network Traffic in Mojokerto - Yoga Pratama Wijianto; Hendrata Wibisana; Aulia Dewi Fatikasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The growth of industrial estates in the Mojokerto region contributes positively to the economy but has negative impacts on the road network, degrading its performance. Factory operational activities, particularly during shift changes, result in sudden traffic loading (shock loading) and significant mixed traffic on access roads. This study aims to evaluate the traffic impact of factory development on the performance of surrounding roads. Data collection was conducted through primary surveys (traffic volume, side friction, and road geometry) and secondary data. Road performance analysis follows the 2023 Indonesian Highway Capacity Manual (PKJI) to determine Capacity (C) and Degree of Saturation (DS), followed by an ANOVA statistical test and spatial mapping in QGIS. The ANOVA results (p-value < 0.05) confirmed a significant difference among the five factory locations in terms of volume, side friction, and degree of saturation. Spatial mapping of the Level of Service (LoS) revealed significant polarization in existing conditions. The most critical conditions are concentrated in the northern area (PT Mertex Indonesia, PT Mago Pasifik Abadi, and PT Ajinomoto Indonesia), with DS values exceeding 1.0. The southern area (PT Sunrise Steel) is in a transitional phase approaching saturation (DS 0.76), characterized by very high side friction due to frequent employee crossings, logistics vehicle activity, and on-street parking.Conversely, the city roads around PT Intidragon Suryatama are the only areas with stable and smooth traffic performance, with a DS value below 0.50. The resulting thematic map provides a comprehensive visual representation of the current congestion point distribution as a foundation for mitigating industrial traffic impacts Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action